An Analysis of Students’ Reading Comprehension Based on The Four Levels Comprehension Skills ( A Study at The Second Year Students of SMAN 10 Bengkulu Academic Year 2014/2015) - Dian Permata Sari (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2016)
The main focus of the study was to describe how students’ reading ability in comprehending English text based on the four levels comprehension skill and what levels do most students’ get comprehending the texts at the second year students of senior high school. The population of this research was all of students of the second year of SMAN 10 Bengkulu in academic year 2014/2015. Random sampling was used to take the sample which consisted of 30 students of the second year students. It was used descriptive quantitative method. In collecting the data, the researcher used reading test based on the four level comprehension skills. The result of this study showed that, only small number of students were successful in answering the questions in interpretive and critical level. It is because students were difficult to find the main ideas and drawing conclusion that also expressed indirectly. However, mostly of students could answer the questions in literal and creative level. It is because the ease of the text and the information also directly stated. The finding is also supported by statistical analysis showed that, the mean score of literal level was (93.33). It means that literal level was on very good category. The mean score of interpretive level was (53.33). It means that interpretive level was on low category. The mean score of critical level was (36.67). It means that critical level was on failure category. While, the mean score of creative level was (72.00). It means that creative level was on moderate category. It is conclude that students more comprehensive when they face English text based on the literal and creative levels than interpretive and critical levels.